Influence of inspiratory muscle strength on 6-minute walk distance in patients with acute heart failure - Ren Takahashi; Junichi Yokota; Yuko Matsukawa; Keisuke Matsushima; Takeru Suzuki; Eiki Tsushima (PLoS ONE, 2025)
Inspiratory muscle weakness may affect exercise tolerance; however, the relationship between inspiratory muscle strength and the 6-minute walk distance (6MWD) in patients with acute heart failure (AHF) is unknown. This study aimed to quantitatively investigate the association between inspiratory muscle strength at the start of cardiac rehabilitation (CR) and 6MWD at discharge in patients with AHF. This single-center, retrospective, observational study enrolled 275 patients with AHF who underwent CR. Patients unable to walk before admission, with isometric knee extensor strength/weight (%IKES) < 0.3 kgf/kg at the start of CR, or unable to undergo examination were excluded. Maximum inspiratory mouth pressure (PI-max) was used as an indicator of inspiratory muscle strength and was measured at the start of CR. The measured PI-max was divided by the predicted value and used for analysis (%PI-max). The primary outcome was 6MWD, an indicator of exercise tolerance, and was measured at discharge. Statistical analysis was performed using multiple regression analysis, with 6MWD at discharge as the dependent variable and %PI-max at the start of CR as the independent variable. Covariates were age, New York Heart Association class, physical frailty, and %IKES at the start of CR. The final analysis included 94 patients (median age 83.0 years, 57.5% male). Multiple regression analysis showed that %PI-max at the start of CR was significantly associated with 6MWD at discharge even after adjustment for covariates (β =  0.223, 95% confidence interval: 0.063–0.382, p =  0.007). PI-max was a factor associated with 6MWD at discharge in patients with AHF. In conclusion, increased inspiratory muscle strength may contribute to improved 6MWD in patients with AHF.